2017
DOI: 10.6061/clinics/2017(07)09
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of narrow-band imaging for early and invasive lung cancer: a meta-analysis

Abstract: This study aimed to compare the ability of narrow-band imaging to detect early and invasive lung cancer with that of conventional pathological analysis and white-light bronchoscopy. We searched the PubMed, EMBASE, Sinomed, and China National Knowledge Infrastructure databases for relevant studies. Meta-disc software was used to perform data analysis, meta-regression analysis, sensitivity analysis, and heterogeneity testing, and STATA software was used to determine if publication bias was present, as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
6
0
1
Order By: Relevance
“…For another commonly addressed bronchoscopic technique in the field of lung cancer screening which is NBI, a relatively recent meta-analysis published in 2017 and based on four studies found that the pooled sensitivity of NBI to detect lung cancer was 91% (both CIS and invasive lesions) compared to a pooled sensitivity of WLB of 70% [44][45][46][47][48]. In one of these four studies, Herth et al compared AFB and NBI in the detection of intraepithelial neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…For another commonly addressed bronchoscopic technique in the field of lung cancer screening which is NBI, a relatively recent meta-analysis published in 2017 and based on four studies found that the pooled sensitivity of NBI to detect lung cancer was 91% (both CIS and invasive lesions) compared to a pooled sensitivity of WLB of 70% [44][45][46][47][48]. In one of these four studies, Herth et al compared AFB and NBI in the detection of intraepithelial neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Đồng thời, nó cũng có thể đánh giá sự xâm lấn của khối u và hướng dẫn chiến lược phẫu thuật điều trị trong các tổn thương đường thở trung tâm. Tổng hợp kết quả từ 6 nghiên cứu, Zhu J. và CS đã đưa ra bảng tổng kết đánh giá độ nhạy và độ đặc hiệu của nội soi dải sáng hẹp trong chẩn đoán sớm UTP (Bảng 4) [13].…”
Section: Nội Soi Phế Quản Dải Sáng Hẹpunclassified
“…FIGURE 3 Follow-up at 2 years: a) computed tomography scan and b) bronchoscopy with narrow band imaging (NBI) to check for local recurrence. NBI uses a unique filter to select light wavelengths that are preferentially absorbed by haemoglobin, thereby permitting superior microvasculature detection compared with conventional bronchoscopy [62]. As angiogenesis occurs preferentially in dysplastic or neoplastic lesions, NBI aids in early assessment of local recurrence.…”
Section: Case Reportmentioning
confidence: 99%